Deadenylation and translation regulation of nanos mRNA in Drosophila embryo extract: [kumulative Dissertation] - Jeske, Mandy (2010)
Drosophila; Embryonalentwicklung; in vitro; Translationsregulation; Deadenylierung; nanos-mRNA; Smaug; Oskar